Competitiveness and ecological impacts of green energy technologies: Firm-level evidence for the DACH region - Michael Peneder; Spyros Arvanitis; Christian Rammer; Tobias Stucki; Martin Wörter (Austrian Institute of Economic Research (WIFO), 2017)
For a large sample of enterprises in Germany, Austria and Switzerland (the "DACH" region) we study the impact of policy instruments such as energy-related taxes, subsidies, standards and negotiated agreements, or other regulations on the firm's ecological and economic performance. To identify the causal linkages, we build a system of twelve equations, first tracking the impacts of policy on the adoption of green energy technologies for distinct areas. In a second set of equations, we estimate the perceived impacts of adoption on the firm's energy efficiency, carbon emissions and competitiveness. The results confirm a differentiated pattern of channels through which policy can affect the firm's energy efficiency and carbon emissions, while having a neutral impact on its competitiveness.
Keywords: Q48; Q55; O13; O25; O33; 330; Environmental policy; energy efficiency; technology adoption; innovation; Porter hypothesis